Subcortical syntax: Reconsidering the neural dynamics of language - Murphy, Elliot; Hoshi, Koji; Benítez-Burraco, Antonio (Journal of neurolinguistics, 2022)
Subcortical contributions to core linguistic computations pertaining to syntax-semantics remain drastically under-studied. We critique the cortico-centric focus which has largely accompanied research into these higher-order linguistic functions and suggest that, while much remains unknown, there is nevertheless a rich body of research concerning the possible roles of subcortex in natural language. Although much current evidence emerges from distinct domains of cognitive neuroscience, in this review article we attempt to show that there is a clear place for subcortex in models of natural language syntax-semantics, including a role in binary set-formation, categorized object maintenance, lexico-semantic processing, conceptual-to-lexical transformations, morphosyntactic linearization, semantic feature-binding, and cross-cortical representational integration. In particular, we consult models of language processing relying on oscillatory brain dynamics in order to investigate both the apparent and possible functional roles of subcortex in language. •We review apparent and possible roles for subcortical structures in natural language syntax.•Core linguistic computations such as binary set-formation and categorized object maintenance are subserved by subcortex.•Cross-frequency oscillatory interactions are highlighted to ground formal properties of language within neural systems.